PROMIS and legacy measures compared in a supportive care intervention for breast cancer patients and caregivers: Experience from a randomized trial. Issue 9 (17th July 2018) - Sikorskii, Alla; Victorson, David; O'Connor, Patrick; Hankin, Vered; Safikhani, Abolfazl; Crane, Tracy; Badger, Terry; Wyatt, Gwen
Abstract: Objective: Accurate and efficient measurement of patient‐reported outcomes is key in cancer symptom management trials. The newer Patient Reported Outcomes Measurement Information System (PROMIS) and previously developed measures of similar conceptual content (legacy) are available to measure symptoms and functioning. This report compares the performance of two sets of measures, PROMIS and legacy, in a recently completed trial of a supportive care intervention that enrolled breast cancer patients and their friend or family caregivers. Methods: Patient‐caregiver dyads ( N = 256) were randomized to either reflexology delivered by caregivers or usual care control. Post‐intervention, PROMIS and legacy measures of symptoms and functioning were analyzed in relation to trial arm, while adjusting for baseline values. Responsiveness of the two sets of measures was assessed using effect sizes and P ‐values for the effect of trial arm on patients' and caregivers' symptom and functioning outcomes. Results: Similar conclusions about intervention effects were found using PROMIS and legacy measures for pain, fatigue, sleep, anxiety, physical, and social functioning. Different conclusions were obtained for patient and caregiver depression: legacy measures indicated the efficacy of reflexology, while PROMIS depression measure did not. Conclusion: Evidence of similar responsiveness supports the use of either set of measures for symptoms and functioning in clinical and general populations. Differences between PROMIS and legacy measures of depression need to be considered when choosing instruments for use in trials of supportive care interventions and in clinical practice.